Evolving Impact of Artificial Intelligence in Human Resource Management in India - Basak, Merry (Digital Repository of Theses, 2025)
Human Resource Management when integrated with Artificial Intelligence creates a different aura altogether. Studies show that Artificial Intelligence in Human Resource Management is creating impact in the workplace as well as work life as a result of which researchers have found out several insights which has resulted in more development. It would not be out of place to mention that researchers have also found out several gaps as well which needs to be further mitigated. The contribution of this study also aims to come up with a new theory which would explore the evolving impact of AI both at transactional and transformational aspects of Human Resource Management and study the level of intervention required to facilitate the process of impact. This research study would help in identifying in which aspect of HRM Artificial Intelligence can replace how much part of human intervention which will keep the trust factor relevant in the organization culture resulting in maintaining a balance between the proper utilization of technological intervention and enhance the productivity in the organization.